Pola Asuh Dan Pola Emosi Anak Balita Yang Ditinggal Kerja Ibu Di Luar Daerah: Studi Etnometodologi dan Interaksi Simbolik Pada Pengasuhan Anak Balita - Choirul Bashor (2001)
The research is inspired by the social phenomenon which describes the problematic relationship between a mother and her children. Actually the mother wants to bring up her children by herself, but in reality, she has to leave her children at home while the mother has to story out of town because of work demand. The fact is that the mother is forced to leave her children in her home town so that the process of bringing up for the children is done by other people such as the father, grandfather, grandmother, aunt, uncle, neighbour, baby-sitters, or others. This process brings about problematic consequences, that is, absorbing norms from the guardian. This condition needs special attention, that's why, data in relation with the process of bringing up children are collected. In the process of bringing up children it is found that the pattern of bringing up the children is in line with the knowledge and the experience of the guardians in applying the norms in the process of bringing up the children. Similarly, in the context of emotional expression, it is found in the research that the children's emotional as in the their various behaviors is the response of children to the guardian's emotional expression in the process of bringing up the children. And it form "emotional pattern" in children which underlies their habits in the next periods. One aspect of guardian pattern is the norms in guardional. The best norms are socialized and they become guidelines for guardians in doing their jobs, while emotional condition formed in the process of bringing up gives psychological input for the children. Thus, it is said that guardian norms applied by the guardians have story effect on the behaviors and personality of children. The guardian pattern is obtained from interactional process between children on their guardian. The interaction itself in the process of the guardian a certain group of society. The norm itself is one of elements in guardional pattern. Thus, guardional pattern belongs to interaction. Researcher gets the mean that the action of bringing up children done by the guardian is based on the society's demand to the guardian who holds the norms in bringing up the children. Taking care of children as a research problem is focused on central issues (I) How does the mother work out of town as a baby-sitter socialized the social cultural values in accordance with the hope of the mother and society in the process of babysitting,? (2) How does the mother work out of town as a baby-sitter take care, guides develope, and control the emotion of children in the process of baby-sitting,? and (3) what is the meaning of the guardional pattern and the emotional pattern according to the sitters.? The objective of this research is to build a concept of the guardian pattern of taking care of the children in which their is socialization of guardional norms in terms of the way the sitter takes care of the children such as, how to awake, how to bath, how to change and put the clothes on, how to take care and accompany the playing, how to make them sleep, and how to give food and drink. It also discusses the emotional pattern of children in terms of how the sitter takes care, guides, developes, and controls the emotion of children. This research uses qualitative methodology with ethnomethodology and symbolic interaction approach. Ethnomethodology paradigm, describes the meaning of guardional pattern and emotional pattern given by the sitter in order that her behavior of teaching norms in the process of taking care can be accepted by the society, aspecially the mother who relies on her in taking care of the children. It also uses symbolic interaction paradigm, in which the actor makes an action in interaction which gives meaning as reality from which the meaning is obtained, and whether the way of taking care is accepted by the mother of the children so that the deal come be continued or not. In fact, guardional pattern is formed in accordance with the sitter's knowledge and experience in applying the norms through the process of taking care. In reality, the emotional condition expressed by children in various behaviors as found out in the research is the children's response to the emotional condition of the sitter in the process of taking care. It forms the emotional pattern in the children which underlies their habits in the next period. From the concepts of guardional pattern and emotional pattern based on the logical consequences in the choice of ethnomethodology paradigm, we can construct the proposition as follows: the pattern of taking care of children under five years is the product of the sitter's knowledge and experience. Whereas emotional pattern of children under five years old is a product of emotional condition which is the children's response to the sitter's emotional condition. Crystallization of conclusional meaning is that the pattern of taking care is formed in accordance with the level of the sitter's knowledge and experience in applying the norms in the process of taking care. The question to be posed is why the level of the sitter's knowledge and experience in using the norms of taking care forms the pattern of taking care. The proposition which are concluded in details are: Proposition 1: The level of the sitter's knowledge and experience underlies the application of norms in taking care of children. The application of norms in taking care determines the patterns in taking care of children. The pattern of taking care is the result of social psychological interaction between children and the sitter. Proposition 2: Emotional condition of the sitter in the process of taking care underlies the emotional condition of children which is expressed in the children's behavior. Emotional condition forms the emotional pattern. The emotional pattern of the children is a result of social psychological interaction between children and the sitter. Theoretical implication of this research is that: every individual has the instinct of taking care which may be the same or different from one individual to another. Similarities and differences according to the concept of taking care found in this research is caused by the inherited pattern of taking care, the differences in the level of knowledge and experience, and the difference in emotional character of sitter. Practical implication in relation with the propositions is the intervention which can be done to the sitter is the conditioning to individuals who care potential in taking care of children through the interaction of teaching and learning.